A STREET THROUGH TIME : A 12, 000-YEAR JOURNEY ALONG THE SAME STREET - Millard, Anne Dr (Dorling Kindersley, 1998)
Traces the development of one street from the Stone Age to the present day, from dirt track to the rebuilding of inns as wine bars, showing how people lived and what they did all day